OUTCOME BASED LEARNING: THE EFFECT OF EXPERIENTIAL LEARNING ACTIVITIES ON THE ATTAINMENT OF SPECIFIC LEARNING OUTCOME AMONG SENIOR SECONDARY SCHOOL STUDENTS - Thote, Prashant; S, Gowri (International Journal of Research -GRANTHAALAYAH, 2021)
Experiential learning activity is a group activity in which the role of an individual is well defined and central focus is on the process and not the outcome. Its process, steps, as well as the content involves active participation of both learners and teachers to attain intended specific learning outcome. In this present paper efforts are made to investigate the impact of experiential learning activity in germinating interests among the students in Chemistry and also to study the co-relation between the interest in studying Chemistry and their academic achievement. The study is conducted during the academic session 2020-2021. Random sampling method is used to draw the sample. Totally 50 students participate in the study. Sample consists of 25 boys and 25 girls. Sample is categorized into the study and the control group. Both groups are taught the unit “Redox Reaction” by traditional lecture method but the study group is exposed to the experiential learning activity designed for the experimental redox reaction. Data is collected by using two questionnaires. Students Interest Test (SIT) and Chemistry Performance Test (CPT) are administrated. Reliability of Students Interest Test (SIT) is done Cronbach Alpha test and found to be 0.86 and reliability test for Chemistry Performance Test by Richardson 21 formula and found to be 0.76. Hybrid research designs such as quasi experiment and survey are applied to collect the data. Data is collected by using pre-test and post-test. The collected data is analyzed by using statistical tools such as independent t-test and Pearson Product Movement to study the co-relation co-efficient. The result of the present study has noteworthy difference of 0.87 significant at 0.05 level. Result of the present paper reveals that the experiential learning activity designed for experimental redox reaction enhances the students’ interest in learning chemistry and has a positive correlation in enhancing their academic performance to attain the specific learning outcomes